Moringa oleifera biopolymer coagulation and bentonite clay adsorption for hazardous heavy metals removal from aqueous systems. Issue 5 (2nd September 2020) - K, Ravikumar; J, Udayakumar
ABSTRACT: Moringa oleifera: seed (MOS) biopolymers and bentonite clay separately have their own heavy metal removal efficiency. However, it is not sufficient for drinking water treatment because of the stringent standards adopted by BIS/WHO. In this study, coagulation with MOS biopolymer and adsorption through bentonite column help in effective removal of heavy metals from the aqueous systems with reduced coagulant dosage at optimum pH conditions. The maximum removal efficiencies of Cd, Cr and Pb are 98.71% at pH 7–8, 99.84% at pH 2–3 and 99.95% at pH 6–7, respectively. The scanning electron microscope, energy-dispersive X-ray spectroscopy and Fourier-transform infrared spectrometer analysis of the sludges of Moringa oleifera and bentonite showed the presence of the metal ions.